Investing in Europe's green future: Green investment needs, outlook and obstacles to funding the gap - Carolin Nerlich; Petra Köhler-Ulbrich; Malin Andersson; Carlo Pasqua; Laurent Abraham; Krzysztof Bańkowski; Tina Emambakhsh; Annalisa Ferrando; Charlotte Grynberg; Johannes Groß; Lucia Hoendervangers; Vasileios Kostakis; et al. (European Central Bank (ECB), 2025)
The green transition of the EU economy will require substantial investment to 2030 and beyond. Estimates of green investment needs vary between institutions and are surrounded by high uncertainty, but they all point to a requirement for faster and more ambitious action. Green investment will need to be financed primarily by the private sector. While banks are expected to make a key contribution to funding the green transition, capital markets need to deepen further, especially to support innovation financing. Progress on the capital markets union would support the green transition. Public funds will be vital to complement and de-risk private green investment. Structural reforms and enhanced business conditions should be tailored to encourage firms, households and investors to step up their green investment activities.
Keywords: E22; E44; G21; Q41; Q50; Q58; 330; green transition; investment; financing; fiscal policy; structural policy